Franz Spaeth: Publications and proposed taxa - Staines, C. L. (Zootaxa, 2005)
Franz Spaeth (1863–1946) was an Austrian lawyer who became an authority on world Cassidinae (Coleoptera: Chrysomelidae). From 1885 until 1961 he published 145 papers in which he described 111 genera and 1212 species. This article presents a brief biographical sketch, a bibliography of his published works, and a list of proposed taxa.